Factors Affecting Dysmenorrhea in Junior High School Students X South Jakarta - Fembriya Tenny Utami (Muhammadiyah International Public Health and Medicine Proceeding, 2021)
One of the menstrual disorders that cause physical discomfort is dysmenorrhea. Dysmenorrhea is menstrual pain that is felt in the lower abdomen and radiates to the pelvis which can interfere with daily activities. The magnitude of the prevalence rate of the incidence of dysmenorrhea, which reaches 90%, and can affect the activities of adolescents during menstruation, so it is necessary to look at the factors associated with the incidence of dysmenorrhea. The purpose of this study was to determine the factors associated with the incidence of dysmenorrhea in junior high school students. The type of research used is observational with a cross-sectional study approach using a questionnaire instrument. The population is all students of SMP 212 South Jakarta. The population of 103 students was obtained by proportional random sampling. The statistical test used was Chi-square with p = 0.05. The results showed the relationship between dysmenorrhea and menarche, length of menstruation, and exercise p>0.05. The results of the statistical analysis test showed that the dependent variables such as age at menarche, duration of menstruation, and lack of exercise were not associated with the incidence of dysmenorrhea because they had a value of Î±> 0.05. The conclusion of this study is that age at menarche, duration of menstruation, and lack of exercise do not affect the occurrence of dysmenorrhea.